The Information Research Department, British covert propaganda, and the Sino-Indian War of 1962: combating communism and courting failure? - McGarr, Paul M. (Taylor & Francis, 2017)
Britain's post-war interventions in former colonial territories remain a controversial area of contemporary history. In the case of India, recent releases of official records in the United Kingdom and South Asia have revealed details of British government anti-communist propaganda activity in the subcontinent during the Cold War period. This article focuses attention on covert or unattributable propaganda conducted in India by the Foreign Office's Information Research Department (IRD). It specifically examines the 1960s: a time between the outbreak of the Sino-Indian border war in 1962, and the Indian general election of 1967, when IRD operations peaked. The Indian government welcomed British support in an information war waged against Communist China, but cooperation between London and New Delhi quickly waned. Britain's propaganda initiative in India lacked strategic coherence, and cut across the grain of local resistance to anti-Soviet material. The British Government found itself running two separate propaganda campaigns in the subcontinent: one focused on Communist China, and declared to the Indian government; and a second, secret programme, targeting the Soviets. In this context, Whitehall found it difficult to implement an integrated and effective anti-communist propaganda offensive in India.